2019
DOI: 10.1186/s13568-019-0775-8
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Listeria monocytogenes in ready-to-eat smoked turkey meat by combination with packaging atmosphere, oregano essential oil and cold temperature

Abstract: The effects of packaging atmosphere, storage temperature and oregano essential oil (EO) on growth of Listeria monocytogenes on ready-to-eat smoked turkey were studied. Smoked turkey slices were inoculated with a strain of Listeria monocytogenes Scott A (5.95, 5.28 and 5.26 log CFU/g) then vacuum packaged (VP), modified atmosphere packaging (MAP: 40% CO 2 and 60% N 2 ) and MAP with oregano essential oil (MAPEO), respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Additionally, the combination effect of packaging atmosphere, oregano EO, and cold temperature on inhibition of L. monocytogenes Scott A in RTE smoked turkey meat was studied by Mahgoub et al They found that inhibition of L. monocytogenes in RTE smoked turkey under MAP and MAP with oregano EO (MAPEO) was increased when compared to VP during the shelf life of the product. They stated that L. monocytogenes can be efficiently controlled by a combination of MAP and oregano EO, especially when it is difficult to keep constant temperature during transportation and retail display (86). The antimicrobial activity of oregano EO has been previously confirmed, and it has been utilized to control L. monocytogenes in meat and meat products (75,(87)(88)(89).…”
Section: Application Of Eos In Meat and Poultry Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the combination effect of packaging atmosphere, oregano EO, and cold temperature on inhibition of L. monocytogenes Scott A in RTE smoked turkey meat was studied by Mahgoub et al They found that inhibition of L. monocytogenes in RTE smoked turkey under MAP and MAP with oregano EO (MAPEO) was increased when compared to VP during the shelf life of the product. They stated that L. monocytogenes can be efficiently controlled by a combination of MAP and oregano EO, especially when it is difficult to keep constant temperature during transportation and retail display (86). The antimicrobial activity of oregano EO has been previously confirmed, and it has been utilized to control L. monocytogenes in meat and meat products (75,(87)(88)(89).…”
Section: Application Of Eos In Meat and Poultry Productsmentioning
confidence: 99%
“…Therefore, the possible adverse sensory effect of high concentrations of EO can be mitigated after synergic treatment (126). Therefore, it could be stated that combined use of EOs as well as their application with other preservative and packaging methods has a synergistic antimicrobial effect on L. monocytogenes in meat and meat products, and further reduction of L. monocytogenes occurred when EOs are associated with these preservative methods (12,31,71,80,84,86,103).…”
Section: Limitations and Future Trends Of Eo Application In Meat And mentioning
confidence: 99%
“…Exploiting the synergy between the antimicrobial activity of the essential oil in a packaging atmosphere suitably modified to reduce microbial growth is an interesting approach because it is relatively simple but does not completely resolve the limits already highlighted for the previous methodologies. The modified atmosphere packaging with EOs system could be efficiently used to control the growth of the pathogen when strict temperature control is difficult during the whole shelf life of the product as demonstrated by Mahgoub and collaborators on a ready‐to eat product inoculated with Listeria monocytogenes . Boskovic and collaborators with the limitation of the negative effect on sensory properties of the treated food successfully reported the synergistic effect of modified atmosphere and thyme EO against four serovars of Salmonella inoculated in minced pork meat.…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 99%
“…The modified atmosphere packaging with EOs system could be efficiently used to control the growth of the pathogen when strict temperature control is difficult during the whole shelf life of the product as demonstrated by Mahgoub and collaborators on a ready-to eat product inoculated with Listeria monocytogenes. [336] Boskovic and collaborators [337] with the limitation of the negative effect on sensory properties of the treated food successfully reported the synergistic effect of modified atmosphere and thyme EO against four serovars of Salmonella inoculated in minced pork meat. In fact, despite an optimal concentration of 0.9 % of EO to obtain the higher antimicrobial activity in combination with the modified atmosphere conditions adopted in the study, only the 0.3 % of EO was considered acceptable by panelists.…”
Section: Uses Of Eos In the Food Industriesmentioning
confidence: 99%
“…Devido a este cenário e aliado ao fato de que certos tipos de alimentos não sofrem nenhum tratamento térmico antes do consumo, torna-se necessário que a cadeia produtora e distribuidora de produtos alimentícios garanta o atendimento dos parâmetros microbiológicos, minimizando o risco da disseminação de doenças transmitidas, bem como formas de controle para redução de contaminações por microrganismos no estágio de processamento e elaboração de alimentos (Mahgoub et al, 2019).…”
unclassified